Teacher’s Grammar: Teaching Beliefs and Practices. A Research on What Second Language Teachers Think, Know, Believe and How It Tallies With Their Practical Methods, Approaches and Standards of Teaching - Mielnik, Kamil (Wydawnictwo Naukowe UAM, 2014)
This study examines the relationship between grammar teaching beliefs and practices. The sample of teachers consists of thirty-tree foreign language teachers. They provided insights into how they are familiarised with teaching methods and approaches and how the grammar is taught in reality. Moreover, the study refers to The Common European Framework of Reference for Languages (CEFR), according to which the practical knowledge should be measured. The nature of teachers’ theories is illustrated with examples from classroom research on grammar teaching. The results suggest that the majority of these teachers possess clearly defined theoretical beliefs, which consistently reflect one particular methodological approach. Some implications of this study for language teacher education are also discussed.
Gramatyka nauczyciela: przekonania i praktyki nauczycielskie. Badanie tego, o czym myślą i co wiedzą nauczyciele języków obcych i stopnia odzwierciedlenia tego w praktyce metodycznej, podejściu i standardach pedagogicznych
Keywords: grammar teaching; second language teaching; communicative language teaching; beliefs; practices